2013
DOI: 10.1080/08351813.2013.780341
|View full text |Cite
|
Sign up to set email alerts
|

The (In)Authenticity of Simulated Talk: Comparing Role-Played and Actual Interaction and the Implications for Communication Training

Abstract: identifying co-present parties) differences were observable in their design and organization.In simulations, actions were more elaborate or exaggerated; that is, they were made interactionally visible and "assessable". Furthermore, some actions were only present in simulations. Implications for the efficacy of role-play methods for training and assessing communication are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
107
0
8

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3
2

Relationship

3
7

Authors

Journals

citations
Cited by 193 publications
(119 citation statements)
references
References 30 publications
4
107
0
8
Order By: Relevance
“…However, as I have discussed elsewhere (Stokoe, 2013b), the authenticity of roleplayed interaction is assumed and asserted, but largely untested. Indeed, I have shown that there are some striking differences between simulated and actual encounters.…”
Section: What Problem Does Carm Address?mentioning
confidence: 99%
“…However, as I have discussed elsewhere (Stokoe, 2013b), the authenticity of roleplayed interaction is assumed and asserted, but largely untested. Indeed, I have shown that there are some striking differences between simulated and actual encounters.…”
Section: What Problem Does Carm Address?mentioning
confidence: 99%
“…In the context of applied CA, CARM has been described as "the most significant … development" (Emmison, 2012). In contrast to traditional role-play, which is steeped in problems of inauthenticity (see Stokoe, 2013b), CARM uses research about actual interaction, and the identification of practices that comprise the setting under investigation, as a basis for training. Workshops focus on, for example, how to convert callers to services to clients of services, as well as other issues including "dealing with -isms".…”
Section: Possible -Isms That Turn Out Not To Bementioning
confidence: 99%
“…bspw. Lalouschek 2002Lalouschek , 2004Lalouschek , 2005Nowak 2010 (Stokoe 2011(Stokoe , 2013(Stokoe , 2014, welcher der "Interventionist applied CA" (Antaki 2011, S. 8) zuzuordnen ist. Ansätze wie jener von Stokoe gehen von einer "coproduction of interventions between academics and practitioners" aus, wobei die berufstätige Person als "the primary owner of expertise" (Hepburn et al 2014, S. 240 The transcript is presented line-by-line, synchronised with the audio file.…”
Section: Gesprächsanalytische Kommunikationstrainingsunclassified